2007
DOI: 10.1266/ggs.82.145
|View full text |Cite
|
Sign up to set email alerts
|

Transposable elements in human cancers by genome-wide EST alignment

Abstract: Transposable elements may affect coding sequences, splicing patterns, and transcriptional regulation of human genes. Particles of the transposable elements have been detected in several tissues and tumors. Here, we report genome-wide analysis of gene expression regulated by transposable elements in human cancers. We adopted an analysis pipeline for screening methods to detect cancerspecific expression from expressed human sequences. We developed a database (TECESdb) for understanding the mechanism of cancer de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
4
0
1
Order By: Relevance
“…28 A causal link between MGEs and carcinogenesis has also been identified as MGE activity may cause genome damage, 12,31,32,33 dysregulation of genome replication or cell cycling, disruption of cooperative cellular behaviour and eventually neoplasia. 34,35,36,37,38 In a recent whole-genome analysis of RNA transcripts using digital gene expression analysis, an increase in satellite repeat marker expression was identified in pancreatic (human and mouse), prostate, lung, kidney and ovarian tumours. 39,40 Of the satellite regions expressed in tumours, MGEs, including LINE-1 (the most abundant MGE in the human genome) were highly enriched.…”
Section: Mobile Genetic Elements and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…28 A causal link between MGEs and carcinogenesis has also been identified as MGE activity may cause genome damage, 12,31,32,33 dysregulation of genome replication or cell cycling, disruption of cooperative cellular behaviour and eventually neoplasia. 34,35,36,37,38 In a recent whole-genome analysis of RNA transcripts using digital gene expression analysis, an increase in satellite repeat marker expression was identified in pancreatic (human and mouse), prostate, lung, kidney and ovarian tumours. 39,40 Of the satellite regions expressed in tumours, MGEs, including LINE-1 (the most abundant MGE in the human genome) were highly enriched.…”
Section: Mobile Genetic Elements and Cancermentioning
confidence: 99%
“…Some MGEs are truly 'selfish' elements. Their reproduction within the genome is deleterious to the rest of the host genome 34 just like any other host-parasite relationship. In the case of MGE fitness, overexpression increases reproduction and underexpression increases viability.…”
Section: Is Mobile Genetic Element Behaviour Disrupted In All Cancers?mentioning
confidence: 99%
“…35 Other researchers have linked HERV-related sequences, such as LINE-1s, SINES and Alus to a variety of cancers, 36 including oesophageal adenocarcinoma. 37 It is too early to confirm any putative role of HERVs and products in such associations, but one study has reported a possible mechanism of HERV-induced malignancy.…”
Section: Hervs In Carcinogenesismentioning
confidence: 99%
“…HERV-H has been found in leukaemia and various cancer cell lines as well as cancers of the lung, stomach, intestine, bone marrow, bladder, prostate and cervix, 22, 23, 24, 25 HERV-K with melanoma, seminomas, the blood of leukaemia patients, teratocarcinomas and breast cancer lines, 26, 27, 28, 29, 30, 31, 32, 33, 34 and HERV-E in prostate carcinoma 35 . Other researchers have linked HERV-related sequences, such as LINE-1s, SINES and Alus to a variety of cancers, 36 including oesophageal adenocarcinoma 37 . It is too early to confirm any putative role of HERVs and products in such associations, but one study has reported a possible mechanism of HERV-induced malignancy.…”
Section: Hervs In Carcinogenesismentioning
confidence: 99%
“…Ένας τρόπος που τα µεταθετά στοιχεία επηρεάζουν τη µεταγραφή των γονιδίων είναι µε την εισαγωγή τους τόσο σε εξόνια όσο και ιντρόνια και τη δηµιουργία πρόωρων θέσεων τερµατισµού, µε αποτέλεσµα να λαµβάνει χώρα εναλλακτική συρραφή εξονίων και ιντρονίων και παραγωγή εναλλακτικών, ηµιτελών, συνήθως µεταγραφηµάτων-πρωτεϊνών (Davis et al 1998, Talamas et al 2006, Kim et al 2007. Επιπρόσθετα, δευτεροταγείς δοµές RNA επηρεάζουν την εναλλακτική συρραφή εξονίων-ιντρονίων (alternative splicing), καθώς µπορεί να εµπλέκονται στην αναγνώριση των θέσεων αποκοπής-συρραφής (Shepard & Hertel 2008).…”
Section: Iv2 τα γονι∆ια Hsp90 του M Galloprovincialis ∆ιαθετουν μια συνθετη ρυθμιστικη περιοχηunclassified